2019
DOI: 10.1111/anu.12913
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of dietary astaxanthin and cholesterol on the growth, pigmentation, fatty acid analysis, immune response and stress resistance of kuruma shrimp ( Marsupenaeus japonicus )

Abstract: A 56‐day feeding trial was carried out to evaluate the interactive effects of chemically synthesized astaxanthin (Ax) and cholesterol (CHO) on the performances of kuruma shrimp juveniles. Six experimental diets containing 2 levels of Ax (0 and 0.6 g/kg diet) and 3 levels of CHO (0, 6 and 20 g/kg diet) were formulated in 2 × 3 factorial design. The results indicated that the interactions between dietary CHO and Ax were not significant on survival, growth performances, body proximate analysis, immune response an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Xing et al (2010) demonstrated that the synthesis of astaxanthin in Phaffia rhodozyma cells was closely related to the metabolism of protein and fatty acids (Xing et al, 2010). Several other studies identified an interaction between astaxanthin and vitamin E, cholesterol or Lactococcus lactis in growth performance, antioxidant capacity and immunity in aquatic animals (Liu et al, 2022; Wang, Ishikawa, Koshio, Yokoyama, Dawood, Hossain, & Moss, 2019; Wang, Ishikawa, Koshio, Yokoyama, Dawood, Hossain, & Zaineldin, 2019; Wang, Xiong, et al, 2019). Some studies have involved the carotenoid‐protein interaction in bird feather coloration, functional food emulsion and crustacyanin (Krawczyk & Britton, 2001; Mendes‐Pinto et al, 2012; Wackerbarth et al, 2009) or considered different levels of protein combined with astaxanthin in diet simultaneously while feeding Cyprinus carpio L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xing et al (2010) demonstrated that the synthesis of astaxanthin in Phaffia rhodozyma cells was closely related to the metabolism of protein and fatty acids (Xing et al, 2010). Several other studies identified an interaction between astaxanthin and vitamin E, cholesterol or Lactococcus lactis in growth performance, antioxidant capacity and immunity in aquatic animals (Liu et al, 2022; Wang, Ishikawa, Koshio, Yokoyama, Dawood, Hossain, & Moss, 2019; Wang, Ishikawa, Koshio, Yokoyama, Dawood, Hossain, & Zaineldin, 2019; Wang, Xiong, et al, 2019). Some studies have involved the carotenoid‐protein interaction in bird feather coloration, functional food emulsion and crustacyanin (Krawczyk & Britton, 2001; Mendes‐Pinto et al, 2012; Wackerbarth et al, 2009) or considered different levels of protein combined with astaxanthin in diet simultaneously while feeding Cyprinus carpio L .…”
Section: Discussionmentioning
confidence: 99%
“…Feeding Cyprinus carpio L . and Hyphessobrycon callistus with a defined amount of astaxanthin increased the activity of antioxidant enzymes significantly (Wang et al, 2006; Wang, Ishikawa, Koshio, Yokoyama, Dawood, Hossain, & Moss, 2019; Wang, Ishikawa, Koshio, Yokoyama, Dawood, Hossain, & Zaineldin, 2019; Wang, Xiong, et al, 2019). GSH‐Px is an important peroxidase decomposing enzyme widely distributed in the body, which is responsible for neutralizing organic and inorganic hydroperoxides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, commercial production of Ast is dominated by synthetic Ast because of its relatively lower production costs compared with the other alternatives ( Saini and Keum, 2018 ). Over the years, an increasing number of reports have revealed the positive correlations between dietary synthetic Ast supplementation and growth performance and survival, or either of them in different species of aquatic animals ( Wade et al, 2017 ; Wang et al, 2019 ). A few studies have been conducted to evaluate the P. rhodozyma Ast on growth performance due to its production capacity limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolymph samples were centrifuged at 4,000 rpm, at 4°C for 10 min, and the serum was separated and collected from supernatants. Weighted hepatopancreas samples were homogenized with shrimp saline solution in an ice-water bath ( Wang et al, 2019 ). After total protein (TP) content was quantified, serum and hepatopancreas samples were used to determine the activities of antioxidant (superoxide dismutase SOD, catalase CAT, total antioxidant capacity T-AOC, and malondialdehyde MDA), and non-specific immune enzymes (aspartate aminotransferase AST, alanine aminotransferase ALT, and alkaline phosphatase AKP).…”
Section: Methodsmentioning
confidence: 99%